Langevin Dynamics Driven by a Telegraphic Active Noise - Um, Jaegon; Song, Taegeun; Jeon, Jae-Hyung (Frontiers in Physics, 2019)
Self-propelled or active particles are referred to as the entities which exhibit anomalous transport violating the fluctuation-dissipation theorem by means of taking up an athermal energy source from the environment. Currently, a variety of active particles and their transport patterns have been quantified based on novel experimental tools such as single-particle tracking. However, the comprehensive theoretical understanding for these processes remains challenging. Effectively the stochastic dynamics of these active particles can be modeled as a Langevin dynamics driven by a particular class of active noise. In this work, we investigate the corresponding Langevin dynamics under a telegraphic active noise. By both analytical and computational approaches, we study in detail the transport and nonequilibrium properties of this process in terms of physical observables such as the velocity autocorrelation, heat current, and the mean squared displacement. It is shown that depending on the properties of the amplitude and duration time of the telegraphic noise various transport patterns emerge. Comparison with other active dynamics models such as the run-and-tumble and Lévy walks is also presented.